Real Estate Investments in Germany
XXVI, 362 p.
Keywords: International real estate investors are shaping events on the German real estate market to an ever greater extent. The reason for the increasing interest of foreign investors in the German real estate market is primarily the property prices which are still low by international comparison and promise above-average returns. The proportion of foreign investors in the transaction volume on the German real estate market suddenly jumped to over 50% in 2005 and this trend has continued in 2006 at an ever increasing rate. The idea behind writing a book in English about real estate investments in Germany was therefore born from practical experience in advising foreign investors. In our opinion it is essential for an investor to know the special legal and tax characteristics and the economic parameters of the German real estate market in order to be in a position to make a sound investment decision. Against this background this book is not to be viewed as a scientific study; the aim of the authors and publishers is to familiarise foreign investors in a comprehensible and practical manner with legal and tax aspects and the economic factors prevailing on the German real estate market.